Second generation enzymatic hydrolysis of wastepaper - Oh, Hui Ching (2025)
The increasing environmental concerns and depletion of fossil fuel reserves have necessitated the exploration of sustainable energy alternatives. This study focuses on second-generation bioethanol production via enzymatic hydrolysis of wastepaper, an abundant lignocellulosic biomass. Wastepaper, predominantly composed of cellulose and hemicellulose, offers significant potential as a feedstock due to its high availability and reduced competition with food sources. Enzymatic hydrolysis using Aspergillus niger and Saccharomyces cerevisiae was employed to convert cellulose into fermentable sugars and subsequently into bioethanol. Key parameters investigated include wastepaper texture (blended and unblended) and weight (5g, 10g, and 15g) to optimize bioethanol yields. Results demonstrate that blending wastepaper significantly enhances hydrolysis efficiency due to increased surface area. Optimal bioethanol production was achieved at a texture-to-weight ratio that balanced substrate accessibility and microbial activity. This research underscores the viability of using enzymatic hydrolysis for bioethanol production from wastepaper, contributing to renewable energy solutions and sustainable waste management practices.